Pemberdayaan Masyarakat Anti Hoax Sebagai Upaya Pencegahan Konflik Identitas di Desa Semangat Dalam - Susanto, Didi; Rico; Hayat, Muzahid Akbar (Prisani Cendekia, 2024)
The Community Empowerment Program Rejecting Hoaxes as an Effort to Prevent Identity Conflict in Spirit Dalam Village aims to increase digital literacy and public awareness of the negative impacts of spreading hoax information. In the fast-paced digital era, people are faced with various information from various sources. Easy access to the internet and social media allows information to spread quickly, including hoax information that has the potential to cause conflict and panic in society. Spirit Dalam Village, even though it is in the countryside, has really felt the impact of the spread of hoax information. Villagers are enthusiastic about using the internet in their daily lives, but many of them do not understand how to verify the veracity of information obtained from the internet or social media. This makes them vulnerable to the spread of hoax information. This program is designed to overcome this problem through digital literacy training and socialization of the negative impacts of hoaxes.